The son of Neptune: the graphic novel (Heroes of Olympus (graphic novels), 2, 1, 2017)
Demigod Percy Jackson, still with no memory, and his new friends from Camp Jupiter, Hazel and Frank, go on a quest to free Death, but their bigger task is to unite the Greek and Roman camps so that the Prophecy of Seven can be fulfilled.

The mark of Athena: the graphic novel (Heroes of Olympus, 3,, 2023)
Uniting with Jason, Piper, and Leo after their dangerous quest, Percy, Hazel, and Frank wonder who'll be chosen to fulfill the Prophecy of Seven, completing their group's number, and sail with them to an ancient land to find the mysterious Doors of Death.